Cognitive Information Systems for Protection of Museum Complexes - Valentinovich Bogdanov, Aleksey; Gennadievich Malygin, Igor (International Journal of Engineering and Technology, 2018)
The paper considers the conceptual provisions of building a promising cognitive information security system of the museum complex on a cyber-physical basis. The stratified model of cognitive information security system of the museum complex was presented. It was shown that the key technological platform for the security of the museum complex is information and network technologies integrated (converged) with the technologies of industrial artificial intelligence. The generalized structural scheme of the cognitive cycle of the information security system of the museum complex was considered. The characteristic of the basic processes realized in a cognitive contour was given. Â Â Â